2002
DOI: 10.1038/nsb863
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and experiment yields the structure of acireductone dioxygenase from Klebsiella pneumoniae

Abstract: Here we report the structure of acireductone dioxygenase (ARD), the first determined for a new family of metalloenzymes. ARD represents a branch point in the methionine salvage pathway leading from methylthioadenosine to methionine and has been shown to catalyze different reactions depending on the type of metal ion bound in the active site. The solution structure of nickel-containing ARD (Ni-ARD) was determined using NMR methods. X-ray absorption spectroscopy, assignment of hyperfine shifted NMR resonances an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
137
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(138 citation statements)
references
References 38 publications
1
137
0
Order By: Relevance
“…While introduction of Nδ ligation of the iron at His 98 into our structural calculations for ARD′ resulted in multiple NOE violations in the active site, such a switch made little difference in calculations of Ni binding in ARD using modeled coordinates (9). It is possible that nickel prefers Nδ ligation at His 98.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While introduction of Nδ ligation of the iron at His 98 into our structural calculations for ARD′ resulted in multiple NOE violations in the active site, such a switch made little difference in calculations of Ni binding in ARD using modeled coordinates (9). It is possible that nickel prefers Nδ ligation at His 98.…”
Section: Discussionmentioning
confidence: 99%
“…In ARD, residues 39-50 form a largely disordered loop between strand D of the β-sandwich and the beginning of the E helix, with few NOEs between residues in this loop and other parts of the protein (9,12). In ARD′, however, this loop becomes more ordered, particularly those residues near the side chain of Tyr 57 on the E helix.…”
Section: A Structural Entropy Switch Between Ard and Ard′mentioning
confidence: 98%
See 1 more Smart Citation
“…The NMR experiments and methodology used for sequential assignment and tertiary structural determination of Ni-ARD have been described previously (Mo et al, 1999;Pochapsky et al, 2002). Determination of residual dipolar couplings was accomplished using 1 H, 15 N HSQC spectra obtained without 1 H decoupling in the indirect dimension on a Varian INOVA 14 T (600 MHz 1 H) NMR spectrometer, Quadrature detection in the indirect dimension was obtained using the Rance-Kay method (Muhandiram and Kay, 1994).…”
Section: Nmr Data Acquisition and Analysismentioning
confidence: 99%
“…The structure of a nickel-binding dioxygenase, acireductone dioxygenase (Ni-ARD) from Klebsiella pneumoniae, was recently determined by NMR and its active site modeled by comparative homology modeling (23). It was suggested that ARD might also be a member of the cupin superfamily.…”
Section: Resultsmentioning
confidence: 99%